Relugolix combination therapy in European women with symptomatic uterine fibroids: a subgroup analysis from the randomized phase 3 LIBERTY pivotal trials - Roberta Venturella; Tomasz Rechberger; János Zatik; Rachel B. Wagman; Emily Zhu; Viatcheslav G. Rakov; Felice Petraglia (Taylor & Francis Group, 2023)
Objective In the 24-week, phase 3 LIBERTY 1 (L1) and LIBERTY 2 (L2) trials, relugolix combination therapy (relugolix-CT (relugolix 40 mg, estradiol 1 mg, norethisterone acetate 0.5 mg)) reduced uterine fibroid (UF)-associated symptoms. This post hoc analysis assessed safety and efficacy of relugolix-CT in European women from L1/L2.Methods Premenopausal women (aged 18-50 years) with UF-associated heavy menstrual bleeding (HMB) were randomized 1:1:1 in L1 (N = 388) and L2 (N = 382) to relugolix-CT or placebo for 24 weeks, or delayed relugolix-CT (relugolix 40 mg then relugolix-CT; 12 weeks each). Primary endpoint: proportion of responders (menstrual blood loss (MBL) <80 mL and reduction of ≥50% from baseline MBL volume) over the last 35 days of treatment. Secondary endpoints: MBL volume, amenorrhea, UF-associated pain, symptom severity, distress related to bleeding and pelvic discomfort, health-related quality of life (HRQoL). Safety endpoints included adverse event (AE) reporting and bone mineral density (BMD) assessment.Results In European women from L1/L2 (N = 124, 16%), a significantly greater proportion of treatment responders was observed with relugolix-CT vs. placebo (85.4% vs. 19.1%, respectively; nominal p < .0001). There were statistically significant improvements with relugolix-CT vs. placebo for several secondary endpoints: reduction in MBL volume, amenorrhea rate, proportion achieving mild-to-no pain, reduction in symptom severity and distress from bleeding and pelvic discomfort, and improvement in HRQoL. Incidence of AEs and percentage changes in BMD from baseline to week 24 were similar for relugolix-CT and placebo.Conclusions In European women with UF and HMB, once-daily relugolix-CT vs. placebo improved UF-associated symptoms and preserved BMD.